2016
DOI: 10.1540/jsmr.52.36
|View full text |Cite
|
Sign up to set email alerts
|

Effects of straight alkyl chain, extra hydroxylated alkyl chain and branched chain amino acids on gastric emptying evaluated using a non-invasive breath test in conscious rats

Abstract: Aim: Some amino acids been known to influence gastric emptying. Thus we have evaluated the effects of straight alkyl chain, extra hydroxylated alkyl chain and branched chain amino acids on gastric emptying. Materials and Methods: Gastric emptying was evaluated in rats after feeding with Racol (nutrient formulae) containing [1-13C] acetic acid. Using a breath test, the content of 13CO2 in their expired air was measured by infrared analyzers. Rats were orally administered with test amino acids, while control rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…6 These findings suggest that the above-mentioned amino acids inhibit gastric emptying. We observed that amino acids with an alkyl chain, hydroxyl group, and branched chain differently inhibited and/or delayed gastric emptying as shown by a breath test, 7 and that L-glycine and L-serine significantly enhanced gastric adaptive relaxation in a barostat study. 8 Based on those findings, we speculated that there is a close correlation between gastric emptying and gastric adaptive relaxation.…”
Section: Introductionmentioning
confidence: 82%
“…6 These findings suggest that the above-mentioned amino acids inhibit gastric emptying. We observed that amino acids with an alkyl chain, hydroxyl group, and branched chain differently inhibited and/or delayed gastric emptying as shown by a breath test, 7 and that L-glycine and L-serine significantly enhanced gastric adaptive relaxation in a barostat study. 8 Based on those findings, we speculated that there is a close correlation between gastric emptying and gastric adaptive relaxation.…”
Section: Introductionmentioning
confidence: 82%
“…The Tmax and Cmax values were significantly delayed and decreased, respectively, as compared with control, but the AUC 120 min value was not. In addition, glycine also significantly delayed and inhibited gastric emptying, with a significant decrease in the Cmax and AUC 120 min as well as a significant delay in the Tmax as compared with the control ( 4 ). Then, we analyzed the correlation between gastric adaptive relaxation and gastric emptying.…”
Section: Discussionmentioning
confidence: 98%
“…The dosage of amino acids (1 g/kg) was identical to that in our earlier study ( 4 ) to allow a comparison between the gastric adaptive relaxation and gastric emptying studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in rodent studies, the effect of isoleucine administration on gastric emptying is less clear. For example, in rats, oral administration of isoleucine reduced the 13 CO 2 content in the breath following a gastric emptying breath test, but did not significantly affect the 13 CO 2 AUC, Cmax, or Tmax values (peak concentration and the time at which it occurred) compared to controls [ 39 ].…”
Section: Discussionmentioning
confidence: 99%